2010
DOI: 10.1007/bf03208878
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference of genetic parameters for test-day milk yield, milk quality traits, and somatic cell score in Burlina cows

Abstract: The aim of the study was to infer (co)variance components for daily milk yield, fat and protein contents, and somatic cell score (SCS) in Burlina cattle (a local breed in northeast Italy). Data consisted of 13,576 monthly test-day records of 666 cows (parities 1 to 8) collected in 10 herds between 1999 and 2009. Repeatability animal models were implemented using Bayesian methods. Flat priors were assumed for systematic effects of herd test date, days in milk, and parity, as well as for permanent environmental,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…However, the heritability estimate for SCS in this study falls within the range (0.04-0.16) reported in the literature for sheep (e.g., Barillet et al, 2001;Baro et al, 1994;Hamann et al, 2004). Using the same Bayesian approach, Penasa et al (2010) obtained a value of 0.05 for Table 1 Descriptive statistics for milk yield and somatic cell score both considering the whole sample and according to the health status (infected or not infected). the SCS heritability in a small autochthonous dairy cattle breed; whereas, other authors found higher values in German Holstein (Hinrichs et al, 2005) and Danish Holstein breed (Madsen and Odegard, 2006).…”
Section: Resultssupporting
confidence: 80%
“…However, the heritability estimate for SCS in this study falls within the range (0.04-0.16) reported in the literature for sheep (e.g., Barillet et al, 2001;Baro et al, 1994;Hamann et al, 2004). Using the same Bayesian approach, Penasa et al (2010) obtained a value of 0.05 for Table 1 Descriptive statistics for milk yield and somatic cell score both considering the whole sample and according to the health status (infected or not infected). the SCS heritability in a small autochthonous dairy cattle breed; whereas, other authors found higher values in German Holstein (Hinrichs et al, 2005) and Danish Holstein breed (Madsen and Odegard, 2006).…”
Section: Resultssupporting
confidence: 80%
“…These preliminary research was fundamental in describing genetic diversity estimates in BUR, but provided only limited and static information on how breed variability and distinctness were developing. Our results spanned a 20-year period including animals from 1991 to 2010 overlapping those recorded by pedigree information (Battagin et al, 2010) and previous molecular studies (Del Bo et al, 2001;Dalvit et al, 2008). The mean MNA value found in BUR (6.46) is comparable to that previously obtained by Dalvit et al (2008) for the same breed (6.70) and to that of IHF (6.35), and larger than the value reported by Del Bo et al (2001) (5.59).…”
Section: General Remarksmentioning
confidence: 97%
“…However, we do not know if this decline occurred as a rapid series of bottlenecks and if the decline in genetic diversity is still ongoing in the breed- ing population. Battagin et al (2010) recently analysed pedigree information of BUR available since 1980. In the last ~30 years the number of recorded individuals increased significantly together with the number of inbred animals; at the beginning of the conservation programme, bulls of the local breed were mated to pure and crossbred Burlina cows and then backcross to Burlina was practiced (Bittante et al, 1992).…”
Section: General Remarksmentioning
confidence: 99%
See 2 more Smart Citations